Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/gels8020136
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Hydrogels Based on a Copolymer of N-Vinyl-2-pyrrolidone and Glycidyl Methacrylate in the Presence of the Reaction Product of 1,3-Dimethylmidazolium Dimethylphosphate and Elemental Sulfur

Abstract: The aim of the study is to search for a reaction that provides the possibility of tandem “one-pot” formation of polymer networks during radical copolymerization of N-vinyl-2-pyrrolidone and glycidyl methacrylate. It was shown that the addition of recently synthesized 1,3-dimethylimidazolium (phosphonooxy-)oligosulfanide makes it possible to obtain a cross-linked copolymer in one stage as a result of radical copolymerization of N-vinyl-2-pyrrolidone and glycidyl methacrylate with a molar ratio of monomers less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…High-polymer-content gel showed the least shrinkage and largest surface area for both drying methods. Moreover, Tarasova et al showed a unique gelation method, which helped to realize the sequences of two or more stages in one reaction [ 12 ].…”
mentioning
confidence: 99%
“…High-polymer-content gel showed the least shrinkage and largest surface area for both drying methods. Moreover, Tarasova et al showed a unique gelation method, which helped to realize the sequences of two or more stages in one reaction [ 12 ].…”
mentioning
confidence: 99%